2018
DOI: 10.1371/journal.pone.0207514
|View full text |Cite
|
Sign up to set email alerts
|

Adult attachment and social anxiety: The mediating role of emotion regulation strategies

Abstract: Despite extensive evidence relating attachment dimensions to maladaptive interpersonal behaviours and dysfunctional emotion regulation strategies, few studies have explored social anxiety in the context of adult attachment dimensions. The aim of the present study was to investigate whether attachment-related anxiety and avoidance are associated with symptoms of social anxiety and whether cognitive emotion regulation strategies (reappraisal and suppression) play a role in the relationship between adult attachme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
31
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(41 citation statements)
references
References 85 publications
6
31
0
1
Order By: Relevance
“…Furthermore, the individual pathways between attachment avoidance and each of the mediators and DV (i.e., thought suppression, self-compassion and depression) were each non-significant. A similar pattern of findings has been reported in previous studies [ 78 , 80 ], wherein the previously significant relationships between attachment avoidance and other study variables were rendered non-significant once attachment anxiety was included as a covariate. One possible interpretation of this finding is that the observed significant effects in the original model were driven by the variance which is common to both attachment dimensions.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Furthermore, the individual pathways between attachment avoidance and each of the mediators and DV (i.e., thought suppression, self-compassion and depression) were each non-significant. A similar pattern of findings has been reported in previous studies [ 78 , 80 ], wherein the previously significant relationships between attachment avoidance and other study variables were rendered non-significant once attachment anxiety was included as a covariate. One possible interpretation of this finding is that the observed significant effects in the original model were driven by the variance which is common to both attachment dimensions.…”
Section: Discussionsupporting
confidence: 88%
“…Given that previous research (e.g., [ 76 , 78 ]) has found a significant association between attachment avoidance and attachment anxiety, it may be such that significant associations observed between either attachment dimension and other study variables are an artefact of the association between the attachment dimensions. To rule out this possibility, the mediation model displayed in Fig 1 (Model A) was run twice, with attachment anxiety entered as a covariate in the second iteration of the analysis.…”
Section: Resultsmentioning
confidence: 97%
“…The analysis strategy does not allow for any definitive conclusions regarding causal relationships, nor does it offer any evaluation of the relative strength of indirect effects attributed to each mediation variable. Consistent with interpretations of differential pattern of significance in the direct and indirect pathways reported in relation to analysis strategies (e.g., Read, Clark, Rock, & Coventry, 2018), it would seem reasonable to suggest that the present study's results may imply that prospective IU and inhibitory IU may operate on worry through distinct pathways; that is, through positive beliefs about worry and negative problem orientation, respectively.…”
Section: Discussionsupporting
confidence: 88%
“…In fact, numerous studies have found that attachment anxiety and emotional dysregulation are positively correlated, and these two variables also appear to contribute to maladaptive behavior and affective problems, such as problematic internet use (Estevez et al, 2018), eating disorders (Norrish et al, 2019), anxiety (Esbjorn et al, 2012; Nielsen et al, 2017), and depression (Marques et al, 2018; Owens et al, 2018; Read et al, 2018). Difficulties in emotion regulation are in particular considered risk factors for both substance (e.g., alcohol and drug abuse) and behavioral addiction (e.g., gambling disorder, video game addiction, and smartphone addiction).…”
Section: Introductionmentioning
confidence: 99%